ОБЗОР МЕТОДИЧЕСКИХ ПОДХОДОВ В ОБУЧЕНИИ ИНОСТРАННОМУ ЯЗЫКУ - Елмуратов, Р.Х.; Асенов, Н.Ж. (SCIENCE and SOCIETY, 2017)
The authors of the article consider the history of some methodical approaches, and describe their advantages and disadvantages in teaching a foreign language. Approaches to describe mechanisms of generalization in “global hypothesis” are given, in conclusion it is stated that the most effective approach in teaching a foreign language, should meet modern demands for developing communicative competence of learners.
Keywords: method; approach; cognitive; deductive; inductive; audiolingual